SAT0045 Antibodies Directed against Endogenous and Exogenous Citrullinated Antigens Pre-Date The Onset of Rheumatoid Arthritis. (15th July 2016) - Johansson, L.; Pratesi, F.; Brink, M.; Ärlestig, L.; D'Amato, C.; Bartaloni, D.; Migliorini, P.; Rantapää-Dahlqvist, S.
Abstract : Background: Anti–citrullinated-peptid/protein antibodies (ACPA) have been detected in individuals pre-dating symptom onset of rheumatoid arthritis (RA), with an initial limited spectrum of reactivities that gradually broadens to different citrullinated substrates typical of RA (1, 2). The recent discovery of NETs as source of citrullinated antigens, and namely citrullinated histones H3 and H4 (3). We have previously described deiminated sequences contained in EBV-derived proteins EBNA1 and EBNA2 as specific targets of ACPA in sera from patients with RA (4). Objectives: The aim was to analyze the evolution of the antibody response predating the symptom onset using citrullinated exogenous (viral peptides) and self (H4 peptides) antigens as substrates to detect ACPA. Methods: A cohort of 521 individuals sampled before symptoms of RA, and 272 population controls were identified as being donors to the Medical Biobank of Northern Sweden; 241 plasma samples from early RA-patients were also collected. ACPA were detected by ELISA on viral citrullinated peptides derived from Epstein-Barr-virus-encoded protein (EBNA1) and EBNA2 (VCP1 and VCP2) and on histone 4 derived peptides (HCP1 and HCP2). Results: Anti-VCP1 antibodies were detected in 10.4% of the pre-symptomatic individuals as compared with 36.1% in early RA; anti-VCP2 in 17.1% vs. 52.3%; anti-HCP1 in 10.2% vs. 37.3%; anti-HCP2 in16.3% vs. 48.5%. Anti-VCP and -HCP concentrations were significantly increased in pre-symptomatic individuals as compared with controls (p<0.001) and increased approaching symptom onset. ACPA specific for HCP or VCP appeared simultaneously (median (Q1-Q3) 5.3 (2.9–8.9) years before symptom onset). Combination of anti-VCP1, -VCP2 and–HCP2 and negativity for -HCP1 yielded a high risk ratio (OR=18.70; 95%CI 2.53–138.47; p<0.004). Anti-VCP2 and -HCP2 antibodies were associated in pre-symptomatic individuals with HLA-SE in particular DRB1*0401 but not with the PTPN22 T-allele. Three PADI3/PADI4 single nucleotide polymorphisms (rs3003444, rs7542629 and rs11800688) were significantly associated with anti-HCP1 antibodies after Bonferroni corrections. Conclusions: Anti-VCP and -HCP antibodies predate symptom onset and predict disease development, but no hierarchy of citrullinated epitopes is clear of the ACPA response. These results suggest that no inciting citrullinated antigen so far described is common to all RA patients; rather data suggest a stochastic mechanism in ACPA production. Anti-HCP1 antibodies were associated with PADI polymorphisms. References: Rantapää-Dahlqvist S, et al. Arthritis Rheum 2003;48:2741–9. Brink M, et al. Arthritis Rheum 2013;65:899–910. Pratesi F, et al. Ann Rheum Dis 2014;73:1414–22. Pratesi F, et al Arthritis Rheum 2006;54:733–41 Disclosure of Interest: None declared